2019
DOI: 10.7554/elife.42475
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic control shows that kinetic proofreading regulates the activity of the T cell receptor

Abstract: The immune system distinguishes between self and foreign antigens. The kinetic proofreading (KPR) model proposes that T cells discriminate self from foreign ligands by the different ligand binding half-lives to the T cell receptor (TCR). It is challenging to test KPR as the available experimental systems fall short of only altering the binding half-lives and keeping other parameters of the interaction unchanged. We engineered an optogenetic system using the plant photoreceptor phytochrome B (PhyB) as a ligand … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 86 publications
10
116
1
Order By: Relevance
“…Calcium actuators that trigger aggregation of stromal interaction molecule 1 (STIM1) can provoke DC activation or augment CD8 + T cell cytotoxicity [69,70]. Chemokine secretion [71] or TCR signaling [72,73]…”
Section: Resultsmentioning
confidence: 99%
“…Calcium actuators that trigger aggregation of stromal interaction molecule 1 (STIM1) can provoke DC activation or augment CD8 + T cell cytotoxicity [69,70]. Chemokine secretion [71] or TCR signaling [72,73]…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments demonstrate that AvidCARs with low-affinity antigen-binding domains require bivalent interaction to be efficiently triggered. Such behavior can be explained by the fact that CAR signaling, i.e., the sufficient phosphorylation of signaling proteins, requires a certain duration of interaction with its target antigens, as has been shown for the TCR and other immunoreceptors 39,[53][54][55] . For low-affinity binding domains, this duration is too short in a monovalent interaction and must be prolonged by interaction via a second binding domain, as supported by both our mathematical model and experimental data, in particular those presented in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…There may be several events involved in kinetic proofreading, each of which could contribute to the time-delay required for ligand discrimination 26,45,46 . Notably, our study has identified an important contributor to kinetic proofreading that might have actionable therapeutic implications by providing a means for enhancing T cell responses to weaker agonists against pathogens that elicit weak responses, or to weak agonist peptides displayed by tumors.…”
Section: Discussionmentioning
confidence: 99%